Clinical study of the efficacy and safety of jamu for hyperuricemia - Triyono, Agus; Novianto, Fajar (University of Muhammadiyah Malang, 2019)
Hyperuricemia is a degenerative disease with a reasonably high prevalence and requires long-term treatment. Clinical research has been conducted to test the efficacy and safety of herbal medicine for hyperuricemia. The research involved 30 subjects who had fulfilled the inclusion and exclusion criteria and conducted with a pre-post test research design. Subjects were treated with herbal medicine for hyperuricemia three times a day for 28 days. From the research, jamu for hyperuricemia was effective in reducing blood uric acid levels from 7.43 mg/dL to 5.72 mg/dL, raising the quality of life score (SF-36) from 78.06 to 81.50, and disappeared of clinical symptoms. Use of herbal medicine for hyperuricemia for 28 days in subjects had no symptoms of severe side effects found and did not interfere with liver, kidney, and blood function.